The Effect of Price and Promotion on Purchasing Decisions for Alexandre Christie Watches in Palembang City - Yohanes, Kris Yehuda; Megawati, Megawati (CV. Publikasi Indonesia, 2024)
In today's digital era, effective Marketing Public Relations (MPR) strategies are crucial for businesses to remain competitive and increase consumer engagement. This research aims to analyse the influence of price and promotion on purchasing decisions for Alexandre Christie watches in Palembang City. The sample includes 100 respondents selected using purposive sampling, and data was collected through questionnaires with a Likert scale. The research employed multiple linear regression analysis using SPSS version 25. The findings reveal that both price and promotion variables significantly and positively impact purchasing decisions, partially and simultaneously. This study contributes to the growing body of literature by highlighting the importance of targeted pricing strategies and digital promotions in influencing consumer behaviour, particularly in the fashion accessory market. The results suggest that businesses should maintain competitive prices and leverage promotions to align with market demands and consumer preferences.